Reconstructing Takaful Participation in Makassar: Integrating Maqāṣid Al-Sharī‘ah, Cultural Embeddedness, and Sociological-Juridical Perspectives - Hasibuddin, Muhammad; Akil, Muhammad; Ardi, Ardi; Susfita, Mira (IAIN Manado, 2025)
Takaful participation in Makassar remains low despite its role as a regional center for Islamic finance, indicating a gap between institutional development and societal acceptance. Existing studies have not fully explained how maqāṣid al-sharī‘ah values intersect with local socio-cultural structures or how social, cognitive, and legal factors shape participation. This study addresses these gaps by examining these dynamics and proposing a culturally grounded reconstruction model. Using a qualitative sociological-juridical approach, data were collected from 22 informants, including takaful agents, religious scholars, regulators, and policyholders, through semi-structured interviews, observation, and document analysis. Analysis followed the Miles Huberman Saldaña interactive model with triangulation to ensure validity. We employed a maqāṣid-based hermeneutical lens to interpret values such as ḥifẓ al-māl and ḥifẓ al-nafs, as well as taʿāwun, alongside the local cultural ethos of siri’ na pacce. Findings indicate that low participation is not due to resistance to Islamic principles, but rather to a misalignment between formal takaful mechanisms and community-based solidarity norms. The study introduces the Maqāṣid Cultural Embeddedness Model, integrating value reframing, institutional collaboration with religious leaders, and community-oriented micro-takaful design. This model provides conceptual and practical guidance for aligning takaful systems with maqāṣid objectives and the socio-cultural realities of Makassar.